Effects of Dietary Lipid Sources on the Growth, Gonad Development, Fatty Acid Composition and Spawning Performance of Broodstock, and Early Larvae Quality of Sea Urchin (Strongylocentrotus intermedius) - Zuo, Rantao; Ning, Yanchang; Di, Weixiao; Heqiu, Yuqing; Song, Jian; Ding, Jun; Chang, Yaqing (Frontiers in Marine Science, 2022)
This study was carried out to investigate the effects of five formulated feeds with different lipid sources (colza oil (CO), fish oil (FO), linseed oil (LO), soybean oil (SO), or palm oil (PO)) and kelp (Laminaria japonica) on the growth, reproductive performance of broodstock, and early larvae quality of sea urchin (Strongylocentrotus intermedius). The experimental diets were randomly allocated to a total of 48 (eight urchins per experimental group) individually cultured S. intermedius(initial weight 90.51 ± 0.82g) and the feeding period lasted for 12 weeks. The results showed that the weight gain rate of female sea urchins fed kelp was significantly higher than those fed formulated feeds while the gonadosomatic index of spawned female sea urchins fed kelp was significantly lower than those fed formulated feeds.S. intermedius broodstock fed FO showed the largest egg diameter and fecundity, which could be due to the abundant n-3 LC-PUFA deposited in the gonads of this group. Sea urchins fed SO showed the lowest fecundity and hatching rate, and the highest inflammation level. Sea urchins fed CO showed the highest content of oleic acid in the gonads and eggs, but the lowest fertilization rate. The highest hatching rate was observed in the kelp treatment, which was comparable to that in the LO and PO but was significantly higher than that in CO, FO, and SO. Before mouth opening, all prismatic larvae showed no significant differences in survival during the first 2 days post hatchery (DPH). At the 3 DPH, the survival of S. intermedius larvae was highest in the FO group, followed by those in the PO group, with the lowest survival observed in the kelp group. Thus, FO was accepted as the most ideal lipid source based on growth, reproductive performance, and early larval quality. These results could contribute to adopting an efficient feeding strategy to promote the reproductive performance and offspring quality by choosing the optimal lipid source for S. intermedius broodstock.